2016
DOI: 10.4103/0973-1296.186344
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of total saponins from Dioscorea nipponica makino on gouty arthritis based on the NF-κB signal pathway: An In vitro study

Abstract: Objective:Dioscorea nipponica Makino is one of the most common used traditional Chinese drugs which are used to treat gouty arthritis (GA). Nuclear factor-κB (NF-κB) pathway plays an important role during this process. In the present study, we investigated the effects of total saponins from D. nipponica Makino (TDN) on NF-κB pathway in interleukin-1β (IL-1β) induced fibroblast-like synoviocytes (FLS).Materials and Methods:FLS were divided into three groups: Normal group, model group, which was given 10 μg/L IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Total saponins from Dioscorea nipponica Makino are the principal components that show antiinflammatory effects. 13,16 Our previous study showed that the content of TDN was 55%, and the UPLC-MS method was used to verify that its main components were dioscin, protodioscin, and pseudo protodioscin. The MTT method was also used to test the active component of TDN.…”
Section: Discussionmentioning
confidence: 99%
“…Total saponins from Dioscorea nipponica Makino are the principal components that show antiinflammatory effects. 13,16 Our previous study showed that the content of TDN was 55%, and the UPLC-MS method was used to verify that its main components were dioscin, protodioscin, and pseudo protodioscin. The MTT method was also used to test the active component of TDN.…”
Section: Discussionmentioning
confidence: 99%